Implementação de sistemas de gestão integrados no setor de construção: estudo de casos brasileiros - Rodrigues, Ivete (2006)
Market pressures, the financiai liberalization programs, production sector deregulation and the diminution of commercial and technical barriers have had a dramatic effect on the industrial competitiveness in Brazil. Changes beyond economic environment, such as social, political and technological ones are also drives for the adoption of new entrepreneurial strategies by the corporations. Those changes reveal that business as usual is not enough in terms of management models for facing the new challenges. The companies have adopted quality (QMS), environmental (EMS), and occupational health and safety (OHS) management systems in order to pursue competitive advantages within the market. To bring visibility to their commitment to these systems, the companies have procured integrated certification in the three of them through ISO 9001, ISO 14001 ANO OHSAS 18001 standards. This move brings up the Integrated Management Systems (IMS's), which is the aim of this work. The construction sector has been chosen due to its specific characteristics such as products uniqueness, high environmental impact and high incidence of labor accidents. To research how the IMS's have been implemented in the construction industry, three companies which are known to have adopted this management model were chosen. We have analyzed the motivation, the implementing process and the certification of the system, the criticai success factors, the barriers and the benefits obtained by adopting the IMS's. The research has confirmed previous studies that demonstrate that the motivation, depending upon the context where the companies are inserted, may be the need of improved competitiveness, legitimation or also the environmental awareness of companies' leadership. The key success factors are, top administration comrnitrnent, efficient communication with stakeholders, availability of resources and the maturity of the teams. The barriers are the excessive attention to financiai results, the complex implementation model, the bureaucratic utilization of the system, lack of maturity and skill in the involved personnel, the size of the projects, the professional competence profile and other different kind of resistances. The introduction of IMS within the companies under scrutiny has been steered by the economic scenario, by the high levei of outsourced personnel participation in the companies and the human resources qualification difficulties. Oespite the barriers and difficulties faced by the projects, the IMS has brought a lot of benefits to the organizations and, as a matter of fact, it has sparked positive returns along the value chain, as the adopting companies tend to be more demanding towards their suppliers.